Coastal Ecological Damage and Family Resilience: An Environment-Based Family Law Perspective - Fathurrahim Fathurrahim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to analyze the causal relationship between coastal ecological damage and the degradation of family law functions, as well as to offer a relevant family law reconstruction model to internalize the principle of environmental sustainability in strengthening the resilience of coastal families. The background of this study is based on the fact that coastal families are social units that are highly vulnerable to abrasion, marine pollution, mangrove degradation, overfishing, and the impacts of climate change. Such ecological damage not only causes an environmental crisis, but also has an impact on economic, health, educational, and social harmony aspects within families. Fisherman families, for example, face declining catch productivity, which has implications for the limited fulfillment of children's rights. On the other hand, family law in Indonesia is still sectoral and private in nature, so it is not yet fully integrated with environmental law or maritime policy. This study finds that family law needs to be reconstructed in order to respond to ecological challenges by internalizing the principles of intergenerational justice, ecosystem protection, and the fulfillment of the right to a healthy environment. This reconstruction is realized through three main approaches: reinterpreting norms to include environmental protection clauses in family law, institutional reform so that courts and family authorities are more responsive to ecological issues, and the integration of local coastal wisdom such as sasi laut and awig-awig into the modern legal framework. The results of this study offer an environmentally-based family law model that not only protects internal household relations, but also makes coastal families both legal subjects and ecological actors in ecosystem restoration. Thus, this study provides a new contribution to the study of family law and environmental law, while offering equitable and sustainable policy recommendations for the resilience of coastal families amid ecological change.